Estudo do BDI sobre o preço de obras empreitadas - Hubaide, Eduardo Jorge (2012)
The BDI, Anglo-Saxon term, \"Budget Difference Income\" means \"an additional difference,\" when a civil works construction company, needs to determine the price for a work to be performed in the regime of global enterprise or contract unit price . In Brazil, adopted the term \"Indirect Costs and Benefits \" and includes all indirect costs considered during the execution of a work. These \"Indirect Costs\", expressed by the BDI, follow no rules to standardize the calculation, however, nowadays, it is possible to reach BDIs expenditures that make up these costs and values, accepted by most of the estimators.This paper presents a review of current methodology of calculating the BDI and analyse the BDIs used by forty three construction companies participating in twenty five bids held by the Federal University of Uberlandia, between the years 2004 to 2009. The main objective of this paper is to present a methodology for apportionment of the Central Administration AC . It is an analysis of various proposals for AC and presented the rationale of the proposed methodology. To validate it, presents the results of case study in one company used the BDI and determined with the use of the proposed methodology.